Determination of Copper and Zinc Pollutants in Ludwigia prostrata Roxb Using Near-Infrared Reflectance Spectroscopy (NIRS). Issue 3 (March 2015) - Ouyang, Aiguo; Jiang, Lixia; Liu, Yande; Jiang, Lihong; Hao, Yong; He, Bingbing
The feasibility of using near-infrared reflectance spectroscopy (NIRS) to determine the concentrations of copper (Cu) and zinc (Zn) in Ludwigia prostrata Roxb plants was investigated. Ludwigia prostrata Roxb plants were grown over a full growth cycle under controlled laboratory conditions in soils contaminated with heavy metals. The Cu and Zn concentrations in 72 L. prostrata Roxb samples were analyzed using fame atomic absorption spectrometry, and NIRS spectra were collected in the 1099–2500 nm range. Five mathematical treatments of the spectral data were compared prior to developing the calibration models ( n = 48) using partial least squares regression methods. The two calibration models for Cu and Zn concentrations were evaluated according to the correlation coefficient of cross-validation ( R cv ) and root mean squares error of cross-validation. The highest R cv and the lowest RMSECV were obtained for Cu (0.9 and 7.24 mg kg −1 ) and Zn (0.94 and 19.17 mg kg −1 ), respectively. The results showed that near-infrared diffuse refectance spectroscopy can be used for the rapid determination of Cu and Zn in leaves of L. prostrata Roxb plants.